Land use changes of coastal wetlands using remote sensing. A case study of Muthurajawela & Anawilundawa wetlands, Sri Lanka - Dahanayake, Harsha Dias; Dahanayaka, DDGL; Hudson, Paul; Wickramasinghe, Deepthi (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Wetlands are confronting significant threats arising from human activities, particularly anthropogenic influences. The alteration of land use and land cover in and around wetlands serves as a clear indicator of the escalating human pressure on these ecosystems. This study employs Geographical Information System (GIS) and Remote Sensing to conduct a spatiotemporal analysis, comparing land use changes in both an urban wetland (Muthurajawela) and a peri-urban wetland (Anawilundawa) and their respective buffer areas in Sri Lanka. The study reveals noteworthy transformations in the extent of water bodies, thick vegetation, other vegetation, settlements, and open areas during the period from 2000 to 2021. The observed changes are particularly profound in the urban wetland. In the Muthurajawela wetland, the core habitat characterized by open water experienced significant conversions into settlements and infrastructure, resulting in an 81% reduction from 2000 to 2010 and a 30% reduction from 2010 to 2021. Similarly, water bodies in the Anawilundawa wetland reduced in size by 12% from 2000 to 2010 and 16% from 2010 to 2021. The results highlight the urban wetland’s more substantial transformation from natural areas to anthropogenic areas, necessitating immediate remedial and restoration action. Given this context, it is imperative to delve further into the trajectories, causes, and drivers of land use changes. This deeper investigation is crucial for developing effective wetland management strategies that support sustainability, environmental stability, and the continued functioning of ecosystems.